2009
DOI: 10.1007/s10549-009-0379-0
|View full text |Cite
|
Sign up to set email alerts
|

Etiologic factors for male breast cancer in the U.S. Veterans Affairs medical care system database

Abstract: The etiology of male breast cancer is largely unknown, reflecting its relative rarity. Although a number of previous studies have suggested relationships with a variety of medical conditions, the results have largely derived from case-control studies and may reflect recall biases. Within the large U.S. Veterans Affairs computerized medical care system database, we had the opportunity to access 26 million hospitaldischarge records over the period and to relate various documented medical conditions to the risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
73
0
10

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 39 publications
1
73
0
10
Order By: Relevance
“…Lifestyle factors such as alcohol intake, smoking, and physical activity level have been investigated as risk factors for MBC; none has consistently been associated with higher risk. Although one small study reported that excessive alcohol consumption was linked to MBC (37), other studies have failed to demonstrate the same (29,38,39). The link between smoking and MBC has also not been clearly demonstrated (29,40).…”
Section: Risk Factors For Mbcmentioning
confidence: 99%
“…Lifestyle factors such as alcohol intake, smoking, and physical activity level have been investigated as risk factors for MBC; none has consistently been associated with higher risk. Although one small study reported that excessive alcohol consumption was linked to MBC (37), other studies have failed to demonstrate the same (29,38,39). The link between smoking and MBC has also not been clearly demonstrated (29,40).…”
Section: Risk Factors For Mbcmentioning
confidence: 99%
“…The other genetic factors include androgen receptor (AR) gene, CYp17, PTEN tumor suppressor gene and CHEK2 mutation (28). Nearly 3% to 7.5% of MBC cases have Klinefelter syndrome (28)(29)(30). In addition to BRCA1 and BRCA2, CHEK2 is a kinase effective in DNA repair.…”
mentioning
confidence: 99%
“…In this analysis, a negative correlation with physical activity was established and having history of a first-degree relative with male breast cancer (relative risk, RR, 1.92; 95%CI 1.24-3.91) and increased body mass index (>30 vs. <25; RR 1.79, 95%CI 1.10-2.91) were found to correlate with increased breast cancer. The factors that influence the ratio of estrogen to androgen, external administration of estrogen or testosterone (32), obesity (29,(33)(34)(35), orchitis/epididymitis (29), presence of a history of prostate cancer treated with estrogen (36) and Klinefelter Syndrome (25,29) increase the risk of male breast cancer. Another study that analyzed the USA Veterans Affairs database detected 642 MBCs (29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is an unique report to classify liver disease, in which the type of liver disease did not affect the incidence of male BC. 13 However, they included patients with non-cirrhotic liver disease, did not distinguish cirrhosis from other liver disease, and the etiologies of liver disease was poorly categorized except alcohol. Even in case reports described the details of subjects, the physical measurements were mostly omitted and cryptogenic cirrhosis was verified in only one case report.…”
mentioning
confidence: 99%